Dramatization “The Swan on the Lake Story” to develop fluency with students from 9th grade A in the afternoon shift at Juan Jose Rodriguez Institute, Jinotepe-Carazo in the second semester 2019. - Aguirre Betanco, Massiel Eunice | Carranza Castillo, Dolia Cristabel | Saavedra López, Darling Saavedra López Darling (Nicaragua | CARAZO UNAN-Managua, FAREM, Carazo , Nicaragua, 2019)
This Research is focused on English Teaching and Learning process in High-school. Speaking ability is considered as one of the most important skills in the acquisition of a foreign language. However, it may be very difficult for secondary school students to develop this Skill. Teachers in high-school struggle with learners who are afraid to speak in the foreign language due to they think classmates will laugh at them and they do not need to feel embarrassed. In the recent years, a lot of innovative activities and techniques have been carried out in order to enhance this difficulty. Additionally, English has become an important tool for people´s life due to society is demanding this language as significant to face a role in the community. There are a lot of methodological strategies that teachers may apply in the classroom to encourage students te learn this powerful language, and help them to develop fluency in their English Speech. This paper presents an interactive and creative activity that has been used in other contexts which is Dramatization “The Swan on the Lake Story” to develop fluency with students from High-School. This proposal provides more interactive classes and funny moments to students, succeeding communication between students and teachers. Key words: English Learning and Teaching, Dramatization, Language, High-School
Seminario-(Licenciado en Inglés)-Universidad Nacional Autónoma de Nicaragua
Keywords: Dramatización-Historia del cisne en el lago | Instituto Juan José Rodríguez-Jinotepe | Inglés-Seminario-2019